Presentations and outcomes of people with unexplained symptoms in acute general surgery: protocol for a mixed-methods study. Issue 2 (6th April 2023) - Romeu, Daniel; Taylor, Anna K; Guthrie, Elspeth; Peckham-Cooper, Adam; Henderson, Max; Toogood, Giles
Abstract: Introduction: Unexplained symptoms are common across healthcare settings and are associated with increased mental and physical morbidity and healthcare expenditure. Improving the identification, explanation and management of unexplained symptoms will be helpful to patientsand healthcare systems. Limited data exists exploring unexplained acute abdominal pain in the surgical setting. Objectives: This protocol describes three interlinked studies. Study one will determine the prevalence of anxiety and depression in patients presenting with explained and unexplained abdominal pain in an acute surgical setting. Study two will explore how the explanation and management of unexplained symptoms is conveyed to patients. Study three will explore how patients with unexplained symptoms understand these explanations. Methods and analysis: Patients aged ≥18 years who present to a surgical same day emergency care unit with acute abdominal pain will be eligible. In study one, participants will be asked to complete a questionnaire, including validated self-report measures, at the time of presentation and six months later. They will be divided into explained and unexplained symptom groups based on clinical presentation and investigation outcomes. The proportion in each group meeting diagnostic thresholds for anxiety and depression will be compared and baseline predictors of pain and quality of life six months later will be determined. In study two, recordings of consultations between patients and surgeons involving the explanation and management of unexplained abdominal pain will be analysed. In study three, participants will be interviewed to explore their experiences and understanding of their symptoms.